The Role of Sales Promotion, Experiential Marketing, and Store Atmosphere in Driving Purchase Decisions at Alfamart - Nina Melinda Nomseo; Zusrony, Edwin Zusrony; Tri Imaliya; Heni Dwi Listiyaningrum; Feri Lupiana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to examine the influence of sales promotion, experiential marketing, and store atmosphere on purchasing decisions at Alfamart modern retail stores. The study used a quantitative approach involving a sample of 60 Alfamart consumer respondents living in Semarang Regency, Central Java Province, and sampling using a non-random sampling technique with a purposive sampling method. The research data comes from primary data collected using a questionnaire with an assessment basis using a Likert scale. The data analysis technique used multiple linear regression and was processed using SmartPLS software version 4.1.1.2. The results of statistical tests prove that experiential marketing and store atmosphere have a positive and significant influence in partial tests and simultaneous tests on purchasing decisions at Alfamart modern retail stores. The sales promotion variable does not have a significant impact on purchasing decisions at Alfamart modern retail stores. The results of the study have implications for policy suggestions for Alfamart in improving service quality to increase attractiveness and influence purchasing decisions for customers.